From model to crop: functional characterization of SPL8 in M. truncatula led to genetic improvement of biomass yield and abiotic stress tolerance in alfalfa. Issue 4 (17th October 2017) - Gou, Jiqing; Debnath, Smriti; Sun, Liang; Flanagan, Amy; Tang, Yuhong; Jiang, Qingzhen; Wen, Jiangqi; Wang, Zeng‐Yu
Summary: Biomass yield, salt tolerance and drought tolerance are important targets for alfalfa ( Medicago sativa L.) improvement. Medicago truncatula has been developed into a model plant for alfalfa and other legumes. By screening a Tnt1 retrotransposon‐tagged M. truncatula mutant population, we identified three mutants with enhanced branching. Branch development determines shoot architecture which affects important plant functions such as light acquisition, resource use and ultimately impacts biomass production. Molecular analyses revealed that the mutations were caused by Tnt1 insertions in the SQUAMOSA PROMOTER BINDING PROTEIN‐LIKE 8 ( SPL8 ) gene. The M .  truncatula spl8 mutants had increased biomass yield, while overexpression of SPL8 in M. truncatula suppressed branching and reduced biomass yield. Scanning electron microscopy (SEM) analysis showed that SPL8 inhibited branching by directly suppressing axillary bud formation. Based on the M. truncatula SPL8 sequence, alfalfa SPL8 ( MsSPL8 ) was cloned and transgenic alfalfa plants were produced. MsSPL8 down‐regulated or up‐regulated alfalfa plants exhibited similar phenotypes to the M. truncatula mutants or overexpression lines, respectively. Specifically, the MsSPL8 down‐regulated alfalfa plants showed up to 43% increase in biomass yield in the first harvest. The impact was even more prominent in the second harvest, with up to 86% increase in biomass production compared to the control. Furthermore, down‐regulation of MsSPL8 led to enhanced salt and drought tolerance in transgenic alfalfa. Results from this research offer a valuable approach to simultaneously improve biomass production and abiotic stress tolerance in legumes.